The Validity, Reliability, and Inter-Rater Reliability of Knowledge, Attitude, and Psychomotor Instrument among Health Worker - Ayuningtyas, Pusparini Anggita; Faizatiwahida, Novia; Setiyarini, Sri; Alim, Syahirul (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Health cadres have the potential to play a crucial role in community empowerment and disaster preparedness. Instruments are needed to support the development of comprehensive and efficient earthquake preparedness education programs for health cadres.Objective: This study assess the accuracy and consistency of cognitive, affective, and psychomotor instruments in carrying out earthquake disaster preparedness in health cadres.Methods: A cross-sectional study involving 90 respondents.Results: The results of this study showed that all (n=90) participants were women with an average age of 31 years with an average education of senior high school. All participants were active health cadres. The instrument used in the study was validated through content validity (Pearson Product Moment) and biserial correlation, as well as Cohen's kappa. Utilizing internal consistency reliability, this study found satisfactory inter-item reliability for all cognitive (0.703-0.722) and affective (0.671-0.700) items, as well as all psychomotor items (0.464-1.000).Conclusion: This instrument can be used to measure cognitive, affective, and psychomotor skills of health cadres.